2019
DOI: 10.1080/22221751.2018.1559709
|View full text |Cite
|
Sign up to set email alerts
|

The clinically licensed antifungal drug itraconazole inhibits influenza virus in vitro and in vivo

Abstract: Influenza A virus (IAV) is a common pathogen of respiratory disease. The IAV-induced seasonal epidemics and the sporadic pandemics are associated with high morbidity and mortality. Therefore, effective protection and therapy for IAV infections is an important challenge in countering this public health threat. Because vaccinations only protect against known circulating strains, and the currently available antivirals pose the risk of resistance formation, drugs targeting host cell factors needed for viral replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 60 publications
(75 reference statements)
14
78
0
Order By: Relevance
“…Because the pronounced decrease in SARS-CoV-2 titers observed upon treatment with U18666A hinted at an antiviral capacity of dysregulated endolysosomal cholesterol contents in SARS-CoV-2 infection, we next determined whether fluoxetine treatment of Vero and Calu-3 cells was associated with increased endolysosomal cholesterol pools. We acquired z-stacks from confocal microscopy using CD63 as the specific endolysosomal marker protein (20) (12,13). In line with the images, this quantitative colocalization analysis ( Fig 2B), revealed that fluoxetine at a low concentration of 5 µM caused slightly, yet not significantly elevated cholesterol levels in CD63-positive LELs, whereas treatment with 20 µM fluoxetine induced a prominent and significant endolysosomal cholesterol accumulation.…”
Section: Fluoxetine Treatment Is Associated With Increased Endolysososupporting
confidence: 62%
See 2 more Smart Citations
“…Because the pronounced decrease in SARS-CoV-2 titers observed upon treatment with U18666A hinted at an antiviral capacity of dysregulated endolysosomal cholesterol contents in SARS-CoV-2 infection, we next determined whether fluoxetine treatment of Vero and Calu-3 cells was associated with increased endolysosomal cholesterol pools. We acquired z-stacks from confocal microscopy using CD63 as the specific endolysosomal marker protein (20) (12,13). In line with the images, this quantitative colocalization analysis ( Fig 2B), revealed that fluoxetine at a low concentration of 5 µM caused slightly, yet not significantly elevated cholesterol levels in CD63-positive LELs, whereas treatment with 20 µM fluoxetine induced a prominent and significant endolysosomal cholesterol accumulation.…”
Section: Fluoxetine Treatment Is Associated With Increased Endolysososupporting
confidence: 62%
“…Because our previously published results had revealed that increased endolysosomal cholesterol levels act as an effective antiviral barrier for enveloped viruses, including influenza viruses (12)(13)(14)19), we also tested the impact of a post-infection treatment with U18666A, a small molecule inhibitor of the endolysosomal cholesterol transporter NPC1(17) on SARS-CoV-2 infection. As shown in Fig.…”
Section: Fluoxetine Treatment Impairs Sars-cov-2 Infection In Calu-3 mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies identified the host cell cholesterol homeostasis as a crucial component of the infection process of endocytosed enveloped viruses. Importantly, we verified that the increase in late endosomal cholesterol is embedded in the interferon response against incoming influenza A virus (IAV) particles [12], that this barrier has antiviral capacities when raised pharmacologically [13,14], and that this druggable host cell target can be exploited through repurposed drugs in a preclinical murine infection model [13].…”
Section: Introductionmentioning
confidence: 73%
“…Building on our previous work on the LEL cholesterol balance as a promising therapeutic target for treatment of enveloped viruses [12][13][14]23], we first assessed the antiviral capability of fluoxetine on IAV infection. Because H1N1 and H3N2 subtypes are currently circulating in the human population, Calu-3 cells pretreated with fluoxetine for 16 h were infected with 0.01 MOI of either A/Hamburg/04/2009 (H1N1)pdm09 or A/Panama/2007/99 (H3N2), and the resulting virus titres were measured 24 h p.i.…”
Section: Fluoxetine Treatment Impairs Sars-cov-2 Infection In Calu-3 mentioning
confidence: 99%